ANALISIS FAKTOR YANG MEMPENGARUHI DIVIDEND POLICY DI SEKTOR PERDAGANGAN, JASA DAN INVESTASI - Gabriella, Gabriella; Widyasari, Widyasari (Jurnal Paradigma Akuntansi, 2024)
This research of this study is to discover the effect of collateralizable assets, managerial ownership, leverage, firm size, and investment opportunity on dividend policy in trading, service and investment sector companies listed on the Indonesia Stock Exchange in 2018-2020. Purposive sampling is used as a sampling technique in this study according to predetermined criteria so the sample in this study consisted of 18 companies for 3 periods and obtained 54 sample data. The research methodology used is statistical analysis method. Multiple linear regression analysis is used to test the hypothesis. Data processing in this study using Eviews 12.0 software. The results of this study indicate that firm size had positive and significant effects on dividend policy, while collateralizable assets, managerial ownership, leverage and investment opportunity had no effect on dividend policy.